KERENTANAN DAN RESPON ADAPTIF MASYARAKAT PETANI PADI RAWA LEBAK TERKAIT PERUBAHAN IKLIM DI SUMATERA SELATAN - Rahel Lasmaria Simbolon; Thirtawati Thirtawati; Fauzia Asyiek; Elly Rosana (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2018)
Climate change presents a significant impact on peatland farmer where during the last 5 years has been disrupting the continuity of rice farming in Pinang Mas village. Floods, droughts, and pest attacks increase on their farm has led to a decline in rice production and farmers' income. This study aims to: 1) Measure the level of socio-economic vulnerability and 2) Identifying farmer adaptation strategies. This survey was conducted in Pinang Mas village, Sungai Pinang, Ogan Ilir, South Sumatra. The data was taken in August to October 2015. As many as 65 samples out of 652 households were taken by simple random sampling method. The results of this study indicate that the level of socio-economic vulnerability of farmers by measuring the vulnerability of natural resources, human resources, financial resources, social resources, and physical resources, currently on vulnerable criteria (scored 79.32). Some of the strategies that farmers have done are ecological adaptation strategy by shifting the time of planting, changing the type of seed, rice seed redeem with neighbors or other villagers who had decent planted; economic strategy by selling livestock, switch livelihoods, and reduce consumption, and social adaptation strategies carried out by rely on neighbors and government assistance.